2013
DOI: 10.1007/s11046-013-9716-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pseudogymnoascus destructans Growth from Conidia and Mycelial Extension by Bacterially Produced Volatile Organic Compounds

Abstract: The recently identified causative agent of white-nose syndrome (WNS), Pseudogymnoascus destructans, has been implicated in the mortality of an estimated 5.5 million North American bats since its initial documentation in 2006 (Frick et al. in Science 329:679-682, 2010). In an effort to identify potential biological and chemical control options for WNS, 6 previously described bacterially produced volatile organic compounds (VOCs) were screened for anti-P. destructans activity. The compounds include decanal; 2-et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 21 publications
1
70
0
Order By: Relevance
“…[19]. These microbes are being studied for their biocontrol potential, and our study adds nearly 150 candidate biocontrol agents to this list, Additionally, we expand the list of natural products [18,2023] that could be of potential use in controlling P . destructans in bat caves.…”
Section: Discussionmentioning
confidence: 99%
“…[19]. These microbes are being studied for their biocontrol potential, and our study adds nearly 150 candidate biocontrol agents to this list, Additionally, we expand the list of natural products [18,2023] that could be of potential use in controlling P . destructans in bat caves.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the efficacy of treating bats with anti-fungal chemicals, such as terbinafine, but none have shown any promise. There has also been interest in alternative forms of treatment, including use of naturally occurring bacteria (Fritze et al 2012;Hoyt et al 2015) or volatile compounds (Cornelison et al 2014). Recent work by Cornelison et al (2014) showed that a volatile organic compounds (VOCs) inhibited growth of P. destructans in vitro.…”
Section: Conservation and Managementmentioning
confidence: 99%
“…There has also been interest in alternative forms of treatment, including use of naturally occurring bacteria (Fritze et al 2012;Hoyt et al 2015) or volatile compounds (Cornelison et al 2014). Recent work by Cornelison et al (2014) showed that a volatile organic compounds (VOCs) inhibited growth of P. destructans in vitro. Similarly, a recent study by Hoyt et al (2015) showed that Pseudomonas bacteria that naturally occur on hibernating bats inhibit growth of P. destructans in vitro.…”
Section: Conservation and Managementmentioning
confidence: 99%
“…Advances in antibiotics, fungicides, and probiotics make effective treatment of wildlife diseases more achievable than ever. However, while lab experiments or short-term field trials may produce promising results (e.g., Cornelison et al, 2014), deployment of a given treatment strategy may have unforeseen negative consequences on the host population, especially if host response to the pathogen (or its removal) is not considered in advance. Therefore, it is critical to fully evaluate host-pathogen interactions prior to the deployment of a treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The fungus colonizes bats during an immunosuppressed torpor, but while European bats tolerate infection (Puechmaille et al, 2011), naïve North American bats experience a disruption of physiological homeostasis leading to measureable population declines (Willis et al, 2011;Verant et al, 2014). Severity of these declines has created a sense of urgency for conservation intervention in the form of chemical or biological control (e.g., fungistatic volatile organic compounds; Cornelison et al, 2014), probiotics (e.g., Cheng et al, 2016), or synthetic compounds (e.g., Raudabaugh and Miller, 2015) to either prevent pathogen exposure to naïve populations or reduce disease intensity in infected populations.…”
Section: Introductionmentioning
confidence: 99%